Anaerobic Digestion of Algae Biomass to Produce Energy during Wastewater Treatment. (1st January 2016) - Peng, Shanshan; Colosi, Lisa M.
ABSTRACT: : Water resource recovery facilities (WRRFs) are asked to improve both energy efficiency and nutrient removal efficacy. Integration of algaculture offers several potential synergies that could address these goals, including an opportunity to leverage anaerobic digestion at WRRFs. In this study, bench‐scale experiments are used to measure methane yield during co‐digestion of Scenedesmus dimorphus or mixed WRRF‐grown algae with WRRF biosolids. The results indicate that normalized methane yield decreases with increasing algae content in a manner than can be reasonably well fit using linear regression (R 2 = 67%). It is thus possible to predict methane yield for any mixture of algae and biosolids based on the methane yield of the biosolids alone. Using revised methane yields, the energy return on investment of a typical WRRF increases from 0.53 (without algae) to 0.66 (with algae). Thus, algae‐based wastewater treatment may hold promise for improving WRRF energy efficiency without compromising effluent quality.